2013
DOI: 10.1177/0022427813497963
|View full text |Cite
|
Sign up to set email alerts
|

Breaches in the Wall

Abstract: Objectives: Drawing on theories that emphasize the salience of social ties, this study examines the different kinds of experiences prisoners have with visitation and the implications of those experiences for behavior after release. Method: This study uses data from a release cohort of prisoners to (1) explore how visitation experiences unfold for different cohorts of individuals serving different amounts of time in prison and to (2) test the effects of longitudinal visitation patterns on recidivism. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(32 citation statements)
references
References 55 publications
3
29
0
Order By: Relevance
“…The degree to which participants experienced afforded choice was assessed in eight domains, categorized into four general types: (a) daytime activities (domains: leisure activities, work, education); (b) social networking (domains: receiving visits, making phone calls); (c) physical needs (domains: eating; taking a shower); and (d) religious beliefs (domain: religion/spirituality). These domains were chosen based on consultation with one of the prisons' Psychosocial Service units (responsible for the evaluation of prisoners' possibilities for social reintegration and risk of recidivism; Snacken, Beyens, & Beernaert, 2010) and based on previous empirical studies showing the importance of daytime activities (e.g., Tuastad & O'Grady, 2013), social networking (e.g., Cochran, 2014), physical needs (Vanhouche, 2015), and religious beliefs (e.g., Maitland & Sluder, 1996) for prisoners' well-being. Within each of the aforementioned domains, two questions were asked pertaining to the degree of choice (e.g., leisure domain: "I experience a sense of choice concerning whether or not I am allowed to participate in a leisure activity (for example, sports)").…”
Section: Methodsmentioning
confidence: 99%
“…The degree to which participants experienced afforded choice was assessed in eight domains, categorized into four general types: (a) daytime activities (domains: leisure activities, work, education); (b) social networking (domains: receiving visits, making phone calls); (c) physical needs (domains: eating; taking a shower); and (d) religious beliefs (domain: religion/spirituality). These domains were chosen based on consultation with one of the prisons' Psychosocial Service units (responsible for the evaluation of prisoners' possibilities for social reintegration and risk of recidivism; Snacken, Beyens, & Beernaert, 2010) and based on previous empirical studies showing the importance of daytime activities (e.g., Tuastad & O'Grady, 2013), social networking (e.g., Cochran, 2014), physical needs (Vanhouche, 2015), and religious beliefs (e.g., Maitland & Sluder, 1996) for prisoners' well-being. Within each of the aforementioned domains, two questions were asked pertaining to the degree of choice (e.g., leisure domain: "I experience a sense of choice concerning whether or not I am allowed to participate in a leisure activity (for example, sports)").…”
Section: Methodsmentioning
confidence: 99%
“…Some of their difficulties arise when individuals have problems acquiring housing and employment, avoiding substances, encountering financial difficulties, and experiencing a lack of interpersonal relationships (Bahr et al, 2010; Martinez & Christian, 2009; Petersilia, 2003; Phillips, 2010; Travis, 2005; Visher & Courtney, 2007; Visher & Travis, 2003; Western et al, 2015). Perhaps unsurprisingly, research on prison reentry has shown that individuals with greater levels of social support tend to fare better than individuals who lack social support (Cochran, 2014; Hochstetler, DeLisi, & Pratt, 2010; Mowen & Boman, 2019; Visher, 2004). Existing research has tended to focus on how family, peers, and broader social networks can provide social support for returning individuals.…”
Section: Social Support and Prison Reentrymentioning
confidence: 99%
“…Similar findings exist for peers and social networks. For example, Cochran (2014) found that individuals who were able to maintain connections with their social networks outside of prison reported having lower rates of offending than individuals whose social ties were cut during incarceration. In this case, individuals who left prison received social support via their social network, which aided in the reentry process.…”
Section: Social Support and Prison Reentrymentioning
confidence: 99%
“…Sustaining social ties is an important reintegrative factor (Cochran, 2014, Scoones, Willis, & Grace, 2012. It might, therefore, be argued, that there can be a resocialization effect from EM (as opposed to a rehabilitation effect); our fairly well-integrated target group may possibly have benefited from the EM-intervention because it facilitated an earlier than otherwise return to their social environment and the regaining of employment.…”
Section: Does Em Have Rehabilitative Potential?mentioning
confidence: 98%
“…We also wanted to explore the potential of EM as a means of facilitating social support, since this is a major aspect of reintegration theory. Evidence suggests that social support plays an important practical role in the transition back into society (see Cochran, 2014). Insofar as electronically monitored subjects, especially those in home detention, were enabled to resume their social ties at an earlier date than those still imprisoned, we expected that the experimental subjects would evaluate social support more positively than the control subjects.…”
Section: Procedures and Aim Of The Projectmentioning
confidence: 99%